香港非粵語母語者語言轉移的初步探討: A Preliminary Study of Language Shift of Non-Cantonese Native Speakers in Hong Kong - 梁, 慧敏; 李, 貴生 (人文中國學報, 2012)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文嘗試從社會語言學角度出發，調查在香港工作的非粤語母語人士日常會話中的語言使用情况，探討的範圍包括工作場所和非工作場所中粵語、普通話和英語所占的比重。文章會通過均值分析和變項比較，闡述香港非粤語母語者的語言兼用與轉移的實際情况，并探討語言轉移的背後因素。 This paper aims to investigate the everyday language use of non-Cantonese native speakers who work in Hong Kong from the perspective of sociolinguistics. The three languages, namely Cantonese, Putonghua and English, will be examined closely in terms of their frequency of use in both workplaces and non-workplaces. By comparing the mean scores and related variables, this study further discusses and explains the phenomena of language shift of non-Cantonese native speakers.